Patterns of Thyroid Cancer Mortality and Incidence in Saudi Arabia: A 30-Year Study - Flemban, Arwa F.; Kabrah, Saeed; Alahmadi, Hanaa; Alqurashi, Raghad K.; Turaes, Anwar S.; Almaghrabi, Ruba; Al Harbi, Samah; Khogeer, Asim A. (Diagnostics (Basel), 2022)
Thyroid cancer is the most prevalent endocrine cancer among the female population in the Kingdom of Saudi Arabia (KSA) and the ninth most common in the male population in Saudi Arabia. Over the past years, an increasing incidence of thyroid cancer has been reported in Saudi Arabia. However, the etiology of thyroid cancer is still not clear. Therefore, this study aimed to estimate thyroid cancer incidence and mortality trends in Saudi Arabia from 1990 to 2019. The current study utilized the Global Burden of Disease and the Institute for Health Metrics and Evaluation databases to extract prevalence data of thyroid cancer in Saudi Arabia from 1990 to 2019. Moreover, the current project utilizes Global Burden of Disease (GBD) web-based tools to visualize these data. In total, 23,846 cases (17,220 females and 6626 males) were diagnosed with thyroid cancer in Saudi Arabia from 1990 to 2019. The incidence is higher in females than in males. Over these 30 years, women’s incidence steadily increased by 15-fold versus a 22-fold increase in men. Moreover, there were 2056 deaths in total caused by thyroid cancer in KSA. The mortality rate in women steadily increased by threefold in the same period. However, the increase in mortality was higher in males (sixfold). A high percentage of YLLs was observed in males, with around 24.8% ranging from 30 to 34 and 40 to 45 years. Thyroid cancer incidence rates have increased exponentially between 1990 and 2019. The expansion of the incidence of thyroid cancer in Saudi Arabia could be due to the increased development in detection and diagnosis. The current study provided evidence of the need to increase awareness and diagnosis in the male population.